Comparing social group identifications and socioeconomic deprivation as predictors of psychological distress: Evidence from a Scottish primary care sample. (25th July 2017) - Cientanni, Fabia; Power, Kevin; Sani, Fabio; Wright, Christopher; Baty, Frances; Hustings, Kerry; Morgan, David; Tanner, Gary
Abstract : Social group identification and socioeconomic deprivation have both been linked to self‐reported depressive symptoms in general population samples; however, no study to date has explored the strength of the joint predictive value of these factors within a mental health population. The current study explored the impact of social group identifications and socioeconomic deprivation, together with important clinical and demographic variables, on psychological distress in a Scottish mental health sample. Participants ( N = 976) were recruited from referrals to a computerized cognitive behavioural therapy (cCBT) programme in Scotland, 'Beating the Blues' (BtB) over a 25‐month period. Participants completed the Clinical Outcomes in Routine Evaluation Outcome Measure (CORE‐OM) as a measure of psychological distress and three versions of the group identifications scale (GIS), one for each of three groups: family, community, and a social group of choice. Demographic information and clinical information were collected on commencing BtB. Higher numbers of group identifications were significantly associated with lower psychological distress. Additionally, increased socioeconomic deprivation was significantly associated with more severe psychological distress; however, interestingly, the association was not as strong as that of group identifications. Identifying with fewer social groups predicts more severe psychological symptom presentations, even more so than living in a greater state of socioeconomic deprivation.